PENGEMBANGAN MANAJEMEN MUTU PENDIDIKAN ISLAM BERBASIS TOTAL QUALITY MANAGEMENT (TQM) DI SD TAHFIDZ ISTIQOMAH KAB. AGAM - Mawaddah Al-Mursal, Nurul; Sesmiarni, Zulfani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an implementation handbook for Islamic education quality management based on Total Quality Management (TQM) that is valid, practical, and effective at SD Tahfidz Istiqomah, Agam Regency. The study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The analysis stage was conducted through semi-structured interviews to identify the needs and problems related to educational quality management at the school. The developed product was an implementation handbook containing the concepts of Islamic education quality management, TQM principles, implementation procedures, quality indicators, and monitoring and evaluation instruments. Data were collected through interviews, questionnaires, and documentation. Product validity was assessed by experts using Aiken’s V index, while practicality and effectiveness were measured through user response questionnaires. Data were analyzed using descriptive qualitative and quantitative techniques. The findings revealed that the developed handbook achieved an average Aiken’s V score of 0.90, categorized as highly valid. The effectiveness test showed a percentage score of 80% from the principal, categorized as effective, and 80.97% from teachers, categorized as highly effective. The developed product was considered capable of assisting schools in understanding, planning, and implementing Islamic education quality management systems in a more systematic and sustainable manner. This study contributes to the development of a contextual and applicable TQM-based Islamic education quality management implementation model for tahfidz-based schools.